Wood technologies and uses of Eucalyptus wood from fast grown plantations for solid products - Sanchez Acosta, Martin Miguel; Mastrandrea, Ciro Andres; Lima, José Tarcisio (Society of Wood Science and Technology, 2023)
The forest plantations are replacing the native forest in the wood provision for industries. At world-wide level almost 50% of the provision comes from plantations (IUFRO, TAIPEI 2007), being much greater in the South Cone of South America. Specially in Argentina, Chile and Uruguay the plantations provide more than 85 % of the industrialized raw material. The most important plantations in the South Cone are pines and eucalyptus, having the latter, highest growth (over 30 m3/ha/year, being able surpass 50 m3/ha/year). Eucalyptus initially was planted for energy, cellulose and boards, but in the last years has been adapted for solid uses, replacing in several cases native wood. For this reason, it began to have special importance in Brazil, Chile, Argentina, Uruguay and Paraguay the genetic, silviculture and technological properties uses of this wood. The present paper shows the results of referred studies on technological properties of the fast growth eucalyptus wood, at usual cut ages, also the development in different uses in solid wood products, in the South Cone and other countries.